Practice for Second Language Learning: Don’t Throw out the Baby with the Bathwater - DeKeyser, Robert (International Journal of English Studies, 2010)
After presenting some of the main arguments against certain narrow concepts of second language practice, this article argues that a broader concept of practice, still focused on form or even forms, but with due attention to form-meaning links and with appropriate sequencing of activities to ensure declarative knowledge first, followed by its proceduralization and (at least partial) automatization, is as relevant as ever. A brief overview is given of the range of activities that fall within this concept, and recommendations are made for adaptation to students’ individual and group differences.